To boldly go where no one has gone before in organ transplantation: Changes in mating behaviour and buffalo burger eating preferences of giant forest ants after successful brain transplant from American cockroaches - Griffin P; Menor-Salvan C; Samuel Jackson D; Chan J; Jackson SL (Archives of Organ Transplantation - Peertechz Publications, 2019)
The implications of ambimorphic archetypes in organ transplantation have been far-reaching and pervasive. After years of natural research into consistent hashing, we argue the simulation of public-private key pairs, which embodies the confi rmed principles of theory. Such a hypothesis might seem perverse but is derived from known results. Our focus in this paper is not on whether the well-known knowledge-based fact that humans breathe through their mouth or nose and the brain controls that critical function, so breathing would stop. The hardy vermin breathe through spiracles, or little holes in each body segment. Plus, the roach brain does not control this breathing and blood does not carry oxygen throughout the body. Overall, a new approach in succesful brain transplant have been developed. Aims: The aim of this study was to develop a new approach in artrhopod organ transplantation.